The crystal structures of para-chloriodoxy benzene and some other aromatic compounds - Archer, Elizabeth Muriel (Department of Chemistry, 2016)
The crystal structures of meta-dinitrobenzene, para-chloriodoxy benzene, and benzene iodo-dichloride are described. The structure of meta-dinitrobenzene, C₆H₄(NO₂)₂), was obtained from Fourier projections on the ab and bc planes. The x and y coordinates were obtained with considerable accuracy from the projection on the ab plane, and the z coordinates were obtained from a previous knowledge of the size and shape of the nitro groups and the agreement between the observed and calculated values of F(Okl). The method of three-dimensional Fourier sections was applied to the crystal para-chlor-iodoxy benzene, (ClC₆H₄IO₂), and the coordinates of all the atoms were obtained without any ambiguity. The I-O distances in the iodoxy group are short, which implies the existence of double bonding between the I and O atoms. The main binding forces in the crystal are found to be between neighbouring iodoxy groups. The structure of benzene iodo-dichloride, (C₆H₅ICl₂), has been obtained from Fourier projections on the ac and bc planes. The iodo-dichloride· group is linear. The directions of the covalent bonds of trivalent iodine in C₆H₅ICl₂ can be placed in a trigonal bipyramid, but it was impossible to fit the covalent bonds of pentavalent iodine in ClC₆H₄IO₂ into any simple geometrical figure. These iodine compounds were done in order to determine the valency directions of polyvalent iodine, and to see if there was any relationship between the directions of the covalent bonds in trivalent and pentavalent iodine. If such a relationship does exist, it has not yet been detected.